Pengaruh Kredibilitas Konten Kreator Dr. Detektif Dan Review Produk Terhadap Keputusan Pembelian Konsumen Aplikasi Internasional TikTok Shop Pada Skin Care Glad2Glow - Syifa Auliah; Nidaul Izzah (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. The development of digital marketing through social media such as TikTok Shop has changed the way consumers make purchasing decisions. The phenomenon of the increasing influence of creator content and product reviews is one of the effective marketing strategies, especially in the skincare industry. This study aims to determine the effect of creator content credibility, especially the “Detective Doctor” account, and Product Reviews on TikTok Shop consumer purchasing decisions on the Glad2Glow skincare brand. The research method used is a quantitative approach with purposive sampling technique of 150 TikTok Shop user respondents. Data analysis techniques using multiple linear regression. Hypothesis testing techniques use pre-test and simultaneous test. The results of this study prove that there is a positive and significant effect of Creator Content Credibility and Product Reviews on purchasing decisions. Partially, Creator Content Credibility contributed 57.5% and Product Reviews contributed 71.9% to purchasing decisions. Creator content credibility and product reviews simultaneously influence purchasing decisions by 73.2%, and the remaining 26.8% is influenced by other variables. These findings reinforce the importance of choosing credible content creators and encouraging brands to actively manage consumer reviews. This research is expected to be a reference in developing effective digital marketing strategies in the e-commerce era. Keywords: Content Creator Credibility; Product Review; Purchase Decision.